Answer:
5. X = 2, Y = 3
6. X = 3, Y = 8
Explanation:
For 5, it is easier to use the substitution method to solve. Plug the Y equation into the Y value of the first equation and simplify.
-3x - 2(5x-7) = -12
-3x - 10x + 14 = -12
-13 = -26x
x = 2
Then, plug the X value into either equation.
y = 5(2) -7
y = 3
For 6, it is easier to use the elimination method to solve. Multiply the first equation by 2 in order to eliminate 4y.
10x - 4y = -2
x + 4y = 35
Add these equations and simplify.
11x = 33
x = 3
Then, plug the X value into either equation.
3 + 4y = 35
32 = 4y
y = 8